İki boyutlu ferromagnetik bölgelerin gelişiminin monte carlo metodu ile incelenmesi - Karagöz, Murat (My University, 2002)
İki boyutlu ferromagnetik bölgelerin gelişimini araştırmak için, Monte Carlo metodu kullanarak bu sistemi temsil edecek bilgisayar simülasyonu yapıldı. İlk olarak bir boyutta ferromanyetizmanın olmadığı gözlendi. Daha sonra iki boyuttaki ferromanyetik bölgelerin gelişimini incelemek için gerekli olan bilgisayar simülasyonu geliştirildi. Burada iki boyutlu ferromagnetik bölgelerin gelişimi incelendi. Etkileşme sabiti ve sıcaklığın değerini değiştirerek paramagnetik durumdan ferromagnetik duruma faz geçişlerinin fiziksel özellikleri incelendi. Manyetizasyonun sıcaklığa göre değişim grafikleri elde edildi ve yorumlandı. Son olarak da üç boyutta ferromanyetizmanın oluşması incelendi. CARLO METHOD TO EXAMİNE DEVELOPMENT OF TWO DİMENSİON FERROMAGNETİC REGİONS. To research development of two dimension ferromagnetic regions, using with Monte Carlo Method has been made some computer simulation programs which represent this system. In this research, it is experienced that there is no ferromagnetism in the one dimension. Then, the computer simulation program was developed two examine the two dimension ferromagnetic regions. Here, the ferromagnetic domains with the two dimension were examined. There after, physical properties of the passings of the phases from the paramagnetic state to the ferromagnetic state were examined by changing the constant of interaction and the value of the heat. It was examined that how the phase passing and system magnetism are depend upon the interaction between spins and developing of ferromagnetic regions. Some grafics are gotten when changing heat valve in the magnetic regions. Finally the developping of the ferromagnetism in three dimension was investigated. Nisan, 2002 Murat KARAGÖZ
Keywords: Fizik